Morphology, rheology property, and crystallization behavior of PLLA/OMMT nanocomposites prepared by an innovative eccentric rotor extruder. (28th June 2017) - Wu, Ting; Tong, Yuru; Qiu, Feng; Yuan, Ding; Zhang, Guizhen; Qu, Jinping
Abstract : An innovative eccentric rotor extruder, which can generate continuous elongation flow, was used to fabricate the poly(L‐lactide) (PLLA)/organo‐modified montmorillonite (OMMT) nanocomposites in different OMMT concentrations. The morphology of the nanocomposites was characterized by thermal gravimetric analyzer, X‐ray diffractometer, and transmission electron microscope. The results showed that the OMMT nanoparticles were uniformly dispersed in the PLLA matrix and mainly existed in intercalation mode. The intercalation and exfoliation process of OMMT in the eccentric rotor extruder may be a double‐side exfoliation, which is more effective than the layer‐by‐layer peeling mechanism based on the shear flow. The influence of OMMT on the rheological behavior of PLLA was investigated by dynamic rheological measurements, showing greater improvement of rheological properties for the nanocomposites. The thermo‐mechanical properties analysis indicated that significant enhancement of E′ can be seen for all the nanocomposites. Presence of intercalated OMMT platelets did not lead to a significant shift of the E″ and tan δ curves compared with that of pure PLLA. The crystallization and melting behavior was studied by differential scanning calorimetry, which indicated that the incorporation of OMMT nanoparticles slightly increased the crystallinity of PLLA matrix. The polarizing microscope was further carried out and showed that the dispersed OMMT nanoparticles acted as a heterogeneous nucleating agent to promote the crystallization of PLLA.